Ethics, Trust, and Governance in Temporary Organizations. Issue 4 (16th July 2014) - Müller, Ralf; Turner, Rodney; Andersen, Erling S.; Shao, Jingting; Kvalnes, Øyvind
ABSTRACT: We investigate the influence of governance structures of temporary organizations on the ethical issues faced by its managers, how they respond to these issues, and how that influences trust among stakeholders. A global, web‐based survey confirmed earlier research that project managers encounter transparency, optimization, and relationship issues, and identified four additional ethical issue types. Managers' behavior in responding to ethical issues varies by governance structure, their willingness to resolve ethical issues themselves, and the trust between stakeholders. Higher levels of trust are found in stakeholder‐oriented governance, which can reduce transaction costs. Implications for practitioners and academics are discussed.